Prediction of high efficiency ZnMgO/Si solar cells suppressing carrier recombination by conduction band engineering. Issue 3 (27th December 2012) - Knutsen, K. E.; Schifano, R.; Marstein, E. S.; Svensson, B. G.; Kuznetsov, A. Yu.
Abstract A significant conduction band offset appearing in n‐ZnO/p‐Si heterojunction solar cells is recognized as a serious roadblock to obtain high efficiency solar cells. By alloying with Mg, the conduction band in Zn1–xMgxO can be raised above that of Si, so that the influence of recombination centers at the interface between the two materials is strongly reduced, enabling high efficiency despite recombination velocities as high as 106 cm s−1. By simulating these phenomena we predict an optimal design of a n‐Zn0.8Mg0.2O/p‐Si solar cell resulting in high conversion efficiencies.